Morphological and Histological Study of The Tongue in Rock Pigeon Columba livia gaddi Gemlin, 1789 - Iman S. Al-Jumaily; Entidhar M. Mnati; Baydaa H. Mutlak; Hussain A.M. Dauod (Journal of Madenat Alelem University College, 2013)
The present study aimed to recognize the morphological description and histological structure of the tongue in rock pigeon Columba livia gaddi using light microscope. Ten adult rock pigeon of both sexes were used in this study. Results of the present study showed that the tongue is characterized by an elongated triangular format. Three parts are distinguished in the dorsal surface: the apex the body and the root. On the dorsal surface of the apex and body a median groove is found. Large conical papillae are located symmetrically in the form of the letter V at the median line between the body and the root, also there is one large papillae at each half was observed behind the main row of papillae. The mucosa of the tongue is covered by a thick stratified squamous epithelium which is cornified only on the ventral surface. The desquamate cells were observed on the dorsal surface in the lingual apex and body. The tongue was supported by a hyaline cartilage , which extended from the lingual root to the apex. The lingual glands (branched tubulo- alveolar gland) were embedded in the connective tissue of lamina propria of the dorsal surface and extended laterally from the apex to the laryngeal clefts, while the ventral surface devoid of any glandular structure.